Apakah karakteristik komite audit dan independensi dewan komisaris mempengaruhi financial distress? - Valentine Siagian; Boy Daniel Siagian (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
This study examines the effect of audit committee characteristics and independence board of the commissioner on financial distress on companies listed in IDX30. With purposive sampling, there are 70 firm-year observations included as the sample in this study. Then we use logistic regression to run the data. The result of this study shows that audit committee characteristics which measured by the total number of the audit committees, meeting frequency of the audit committee and the accounting background of the audit committee, only the total number of audit committees affect financial distress on companies listed in IDX30, while the other characteristics don't affect financial distress. Empirically, this result shows that the higher the number of audit committees, the more likely the company could avoid financial distress.